2008
DOI: 10.1080/14786410701591986
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypaphorine in the toxicity ofAstragalus lusitanicus

Abstract: Hypaphorine, an alpha-N,N,N-trimethyltryptophan betaine, was isolated, for the first time, from Astragalus lusitanicus Lam. (Fabaceae), a plant highly toxic for lambs and goats. This alkaloid was characterized by NMR and MS analysis. Hypaphorine was previously reported to be a convulsive poison. To confirm the toxicity, it was synthesized and tested in goats. Hypaphorine was shown to be non-toxic for goats even at a high dose of 2 g kg(-1) by oral administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…The quaternary carbon at d 171.2 was assigned to carboxylic group (C-12), exhibited cross peaks with H-10 and H-11. The structure of compound was thus characterized as known a-N,N, N-trimethyltryptophan betaine, trivially known as hypaphorine, which was further confirmed by matching its spectroscopic data with that reported in literature (Kassaoui et al, 2008).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The quaternary carbon at d 171.2 was assigned to carboxylic group (C-12), exhibited cross peaks with H-10 and H-11. The structure of compound was thus characterized as known a-N,N, N-trimethyltryptophan betaine, trivially known as hypaphorine, which was further confirmed by matching its spectroscopic data with that reported in literature (Kassaoui et al, 2008).…”
Section: Resultssupporting
confidence: 53%
“…Hypaphorine was previously reported to be a convulsive poison. However, later studies showed that it is not toxic (Kassaoui et al, 2008). It inhibits root hair tip growth (Dauphin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Three methyl carbons attached to the nitrogen atom were observed as a singlet signal at δ C 52.8, and their methyl protons showed resonance signals at δ H 4.62 (N + Me 3 ). By comparing the 1 H and 13 C NMR spectra data with those reported from literature, 19 compound 8 was identified as a known hypaphorine.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…26 In fungi, hypaphorine is an antagonist against an IAA (indole-3-acetic acid) that inhibits the root hair tip growth and hair elongation. 19 Recent studies 27 have shown that hypaphorine extracted from Impatiens niamniamensis seeds was an antihyperglycemic agent and showed some activities in streptozotocin-induced diabetic rats. This paper 27 also reviewed previous work where hypaphorine promoted sleep in mice and stimulated the fermentation process in normal male Long− Evans rats that lead to changes in phosphoenolpyruvate carboxykinase activity.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…By mid spring (May) the plants shed their leaves, all above ground plant parts senesce and become dry, and the buried xylopodia become dormant until next winter. Throughout its distribution range populations occur as isolated patches, usually in cork oak (Quercus suber) woodlands from sea level up to 1300 m. The foliage is very toxic to sheep, goats and cattle (Bel-Kassaoui et al, 2008) and for this reason plants are sometimes cut down by shepherds and farmers, presumably to prevent them from spreading (Casimiro-Soriguer, personal observation). Consequently, in parts of its range (particularly Morocco) humans may have decimated populations for centuries.…”
Section: Study Plant Populations Sampled and Dna Isolationmentioning
confidence: 98%